Sources of Psychological Stress of University Students during The Syrian Crisis (A Field Study on a Sample of Tishreen University Students) - Saadi , Rima; Chrebah , Bouchra (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aimed at investigating Tishreen university students’ psychological stress sources. Furthermore, the study attempted to explore whether students differ according to their gender, their academic specializations. The sample of this study comprised of (200) students: (100 male and 100 female). In order to achieve the goals of this study the Inventory of University Students’ Sources of psychological stress was constructed. The final version of the scale consisted of (60) items. These items distributed in seven dimensions: family stress, economic stress, personal stress, security stress, social stress, and environment of the learning stress. The results showed that most areas of the psychological stress is security, and least influential in them are social stress. The results also indicated to significant differences (α≤ 0.05) between males and females means in the social, personal, family, and the economic domains. according to the variable students’ academic specializations, the results showed no differences statistically function (0.05 "≥α) between the students.